Slab Driven Quaternary Rock‐Uplift and Topographic Evolution in the Northern‐Central Apennines From Linear Inversion of the Drainage System - Racano, S.; Beek, P. A.; Schildgen, T. F.; Faccenna, C.; Buleo Tebar, V.; Cosentino, D. (Geochemistry, geophysics, geosystems : G3, 2024)
Investigating rock‐uplift variations in time and space provides insights into the processes driving mountain‐belt evolution. The Apennine Mountains of Italy underwent substantial Quaternary rock uplift that shaped the present‐day topography. Here, we present linear river‐profile inversions for 28 catchments draining the eastern flank of the Northern‐Central Apennines to reconstruct rock‐uplift histories. We calibrated these results by estimating an erodibility coefficient (K) from incision rates and catchment‐averaged erosion rates obtained from cosmogenic‐nuclide data, and we tested whether a uniform or variable K produces a rock‐uplift model that satisfactorily fits independent geochronological constraints. We employ a landscape‐evolution model to demonstrate that our inversion results are reliable despite substantial seaward lengthening of the catchments during uplift. Our findings suggest that a rock‐uplift pulse started around 3.0–2.5 Ma, coinciding with the onset of extension in the Apennines, and migrated southward at a rate of ∼90 km/Myr. The highest reconstructed rock‐uplift rates (>1 km/Myr) occur in the region encompassing the highest Apennine massifs. These results are consistent with numerical models and field evidence from other regions exhibiting rapid rock‐uplift pulses and uplift migration related to slab break‐off. Our results support the hypothesis of break‐off of the Adria slab under the central Apennines and its southward propagation during the Quaternary. Moreover, the results suggest a renewed increase in rock‐uplift rates after the Middle Pleistocene along the Adriatic coast, coeval with recent uplift acceleration along the eastern coast of southern Italy in the Apulian foreland. Plain Language Summary Rivers that drain mountainous regions store information on the history of mountain growth. Specifically, variations in the slope of rivers with distance can be interpreted as variations in the rate at which mountains grow through time. Because changes in slope may also occur due to changes in the hardness of rocks underlying the rivers, we must calibrate and correct our interpretations based on changes in rock type. We use 28 rivers draining the eastern flank of the Northern‐Central Apennines of Italy to reconstruct temporal and spatial variations in the history of mountain growth. We find that a pulse of growth started between 3 and 2.5 million years ago and then migrated southwards through time. This southward movement is most likely associated with tectonic plate dynamics beneath the mountain belt, as the plate plunging beneath the Apennines tore progressively southward. Key Points Spatio‐temporal rock uplift histories inferred from linear inversion of river profiled Impact of variable erodibility coefficient and downstream catchment lengthening on inversion results Quaternary uplift history of the Apennine belt and implications on the driving mechanisms